Rerspective method of cleaning water from toxic substances - Pashchenko, Bohdan (My University, 2020)
The author proposes a promising method of wastewater treatment from toxic pollutants. It involves the combined decontamination from ions of heavy and non-ferrous metals in conditions of hydrodynamic cavitation. Further purification was realized out by ultrafiltration on modules with ceramic membranes. The expediency of this method is substantiated and their results are given in comparison with typical cleaning technologies.

Запропоновано перспективний метод очищення стічних вод від токсичних забруднювачів. Він передбачає комбіноване знезараження від іонів важких і кольорових металів в умовах гідродинамічної кавітації. Подальше очищення здійснювалося шляхом ультрафільтрації на модулях з керамічними мембранами. Обґрунтовано доцільність застосування цього методу та наведено результати у порівнянні з типовими технологіями очищення.
Keywords: кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра експертизи харчових продуктів; department of foodstuff expertise; очищення води; perspective method of cleaning; мембранні технології; cleaning of water; membrane technology; перспективний метод очищення